2003
DOI: 10.1095/biolreprod.103.015941
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles for Hedgehog-Patched-Gli Signal Transduction in Reproduction1

Abstract: Hedgehog (Hh) proteins are expressed during vertebrate development in some tissues with inductive properties and at epithelial-mesenchymal boundaries in several developing organs, including the lung, gut, hair follicle, and tooth. The Hh signaling pathway is highly conserved, and important clues to understanding the mechanism of Hh signal transduction in vertebrates have come from studies in Drosophila. In recent years, Hh signaling has been recognized during embryonic development and in some cases during post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 85 publications
1
27
0
Order By: Relevance
“…These genes are generally involved in tissues requiring cell renewal including induction of cell proliferation, cell survival, and regulation of differentiation. [13][14][15][16] These changes reflect the rapid growth and development of the functional layer of the human endometrium.…”
Section: Microarray Analysismentioning
confidence: 99%
“…These genes are generally involved in tissues requiring cell renewal including induction of cell proliferation, cell survival, and regulation of differentiation. [13][14][15][16] These changes reflect the rapid growth and development of the functional layer of the human endometrium.…”
Section: Microarray Analysismentioning
confidence: 99%
“…It has been shown that the pathway is involved in embryonic development and maturation of Drosophila ovaries, while in the adult fly it is involved in the division of stem cells giving rise to follicles (11). In mammals, the Hh-Gli pathway is also involved in embryonic development of the ovary, and in the adult organism components of the pathway are expressed in reproductive tissues (12). In the adult ovary, the Hh-Gli signaling is active in the granulose cells surrounding the follicle, and it can be additionally activated by exogenous Shh protein (13).…”
Section: Introductionmentioning
confidence: 99%
“…The Hh pathway has been implicated in the development and differentiation of the fetal testis [9] and postnatal and adult ovary [10,11]. In the fetal testis, Sertoli cell-derived DHH is responsible for differentiation of the fetal Leydig cells, the primary steroidogenic cell type in the developing testis [12].…”
Section: Introductionmentioning
confidence: 99%